Chemical Profile and in-silico Docking Studies on Bioactives from Essential Oil of Cymbopogan pendulus Targeting Penicillin Binding Proteins (PBPs) in Bacteria - Arun Dev Sharma; Inderjeet Kaur (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Antibiotic resistance in bacteria is the major concern worldwide. PBP (Penicillin binding proteins) have been cited as an appropriate target for therapeutic drug design. In the present study molecular docking followed by wet lab validation was designed to estimate the effect of potent bioactive molecules from Cymbopogan pendulus essential oil against PBP5 protein. GC-FID (gas chromatography with flame-ionization detection) based composition profile, and in-silico docking study was conducted by using CB-dock 2 analysis followed by 2D and 3D interactions. GC-FID revealed Limonene, Neral, Geranial, Linalool, Myrcene as major and minor compounds in Cymbopogan pendulus essential oil. The docking score indicated effective binding of ligands to PBP5. Interactions results indicated that, PBP5/ligand complexes form hydrogen and hydrophobic interactions. Wet lab study validated the anti-bacterial potential of oil against gram-positive and gram-negative bacteria. Therefore, essential oil from Cymbopogan pendulus essential oil may represent potential herbal treatment to mitigate bacterial infections.